(untitled) (Research, Society and Development, 2024)
Introduction: Diabetes mellitus is a complex metabolic disorder described by chronic hyperglycemia. A decreased production of insulin. In diabetes there are changes in the metabolism of lipids and proteins. There are two main types of diabetes, type 1 and type 2, with several less common secondary types. Periodontal disease is one of the most common chronic inflammatory diseases, which can lead to tooth loss due to the gradual destruction of the connective tissue around the teeth. It occurs mainly in adults and its incidence increases with age. It is an inflammation that spreads and causes tissue destruction and alveolar bone resorption. Objective: This study aims to carry out a literature review in order to elucidate the interrelationship between diabetics and periodontal disease. Methodology: This work consists of a literature review. Results: The findings demonstrate the intricate connection between diabetes and periodontal disease, highlighting the importance of a multidisciplinary approach to treatment. There is general agreement that optimizing communication between professionals and implementing integrated care strategies can not only improve patients’ health outcomes, but also decrease the costs associated with treating these interconnected conditions. Conclusion: The review confirmed the strong interrelationship between diabetes mellitus and periodontal disease, with both negatively influencing each other’s progression. Integration between medical and dental care is essential to improve patients’ glycemic control and periodontal health, highlighting the need for a multidisciplinary approach to treatment.